2012
DOI: 10.1007/s10530-012-0173-5
|View full text |Cite
|
Sign up to set email alerts
|

An assessment of a bait industry and angler behavior as a vector of invasive species

Abstract: The use of live bait by anglers is an important vector of both aquatic and terrestrial invasive species. Bait-bucket introductions of invasive crayfishes, fishes, earthworms, pathogens, and other organisms have reduced biodiversity and altered ecosystem function and structure throughout the United States, including the Mid-Atlantic region. In 2008, we conducted a telephone survey of bait shops and a mail survey of anglers to obtain information on the trade and use of bait in Maryland, a US state with many intr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
108
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 35 publications
3
108
0
Order By: Relevance
“…The bait industry is considered as an important vector of invasive species (Weigle et al, 2005;Haska et al, 2012;Kilian et al, 2012). Kilian et al (2012) reported that 65% of anglers released their unused bait into the water at the end of a fishing trip.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The bait industry is considered as an important vector of invasive species (Weigle et al, 2005;Haska et al, 2012;Kilian et al, 2012). Kilian et al (2012) reported that 65% of anglers released their unused bait into the water at the end of a fishing trip.…”
Section: Discussionmentioning
confidence: 99%
“…Kilian et al (2012) reported that 65% of anglers released their unused bait into the water at the end of a fishing trip. Indeed, Nishi and Kato (2004) reported that Perinereis linea was discarded in Tokyo Bay (Yokohama, Japan) by fishermen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Garcia-Llorente in 2010, found that anglers who were unaware of the impacts of nonnative species were more willing to spread nonnative species than those who were aware. Another study by Kilian in 2012, found that the release of un-used invasive and introduced bait fish is common among recreational anglers who are unaware of potential impacts of invasive species. (Dedual, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, social awareness to the presence of nonnative species can be a tool in the prevention of unintentional introductions of nuisance species (Nuñez & Pauchard, 2010). Surveys of recreational anglers in the US have shown awareness can play a role in limiting the dispersal of nonnative species (Gates et al, 2009, Kilian et al, 2012. Eisworth, et al, (2011) showed that individuals are more likely to be aware of aquatic invasive species if they are active participants in water-based recreation.…”
Section: Introductionmentioning
confidence: 99%